A preliminary study of coarticulation in young Kannada speaking children: A locus equation perspective - Sreedevi N; Vasanthalakshmi MS; Sushma S (Journal of All India Institute of Speech and Hearing, 1970)
This study aimed to determine the developmental patterns of coarticu- lation using F2 locus equation as a metric. Locus equations use the F2 transition to obtain regression lines by plotting onsets of F2 on the y-axis with the F2 midpoint on the x-axis for a given stop consonant across the various vowel contexts. In the present study, coarticulatory in uence ofvowel /a/ over voiced stops in dierent places of articulation [b], [d], [d] and [g] was studied. The participants were native Kannada speakers, 15 children each in the age groups of 4-5 years and 5-6 years. Participants were asked to produce non words in CVCV pattern embedded in a carrier phrase. The recorded utterances were subjected to acoustical analysisusing PRAAT software (Version 5.1.14). In C1V1C2V2 form of stimuli, V1 was the target vowel. The measured F2 values were subjected to regression analysis by considering F2 vowel midpoint as the independent variable and F2 vowel onset as the dependent variable. Extraction of slope values from linear regression revealed higher coarticulation in theyounger group as compared to the older group supporting the holistic theory of coarticulation.